Improving imbalanced learning through a heuristic oversampling method based on k-means and SMOTE - Douzas, Georgios (2018)
Douzas, G., Bação, F., & Last, F. (2018). Improving imbalanced learning through a heuristic oversampling method based on k-means and SMOTE. Information Sciences, 465, 1-20. DOI: 10.1016/j.ins.2018.06.056